Business impacts of event hosting: evidence from the Volvo Ocean Race Finale in Galway 2012. Issue 3 (9th August 2018) - Collins, Patrick; Mulligan, Emer; Cawley, Mary
Abstract : Purpose: This paper sets out to contribute to the growing literature analysing the broader impacts of event hosting. The purpose of this paper is twofold: the first is to add to the growing literature concerned with the spatial impact of immediate (economic) impacts on host locations; the second, in line with the dynamic element introduced by Chalip (2004), is to identify the implications for business leveraging of mega events in the more medium term. Design/methodology/approach: The methodological approach involved analysis of documentary evidence and observational analysis on site before and during the event. The findings are primarily derived from a survey of 150 businesses located across Galway city and its suburbs alongside a thematic analysis of six interviews with the organisers of the event and survey responses. Findings: The authors find that the aspirations to spread the benefits of hosting ultimately proved unsuccessful. Key to this is the power held by global event organisers relative to local organisers. The authors also identify a degree of mismanagement and a lack of adequate support for the organisation of leveraging activities. The authors note a unique geography of impact that does not follow a linear path of decrease from the event site. Originality/value: The work highlights the tensions that can exist between the aspirations of hosting cities and their local organisers against those of international brands responsible for the organisation of global events. The results on the geography of impact also highlight a unique spatial trend, one that sees economic impact increase on the outer limits of the city.